Selective Pd-Catalyzed Monoarylation of Small Primary Alkyl Amines through Backbone-Modification in Ylide-Functionalized Phosphines (YPhos) - Rodstein, Ilja (J Org Chem, 2020)
[Image: see text] Ylide-substituted phosphines have been shown to be excellent ligands for C–N coupling reactions under mild reaction conditions. Here we report studies on the impact of the steric demand of the substituent in the ylide-backbone on the catalytic activity. Two new YPhos ligands with bulky ortho-tolyl (pinkYPhos) and mesityl (mesYPhos) substituents were synthesized, which are slightly more sterically demanding than their phenyl analogue but considerably less flexible. This change in the ligand design leads to higher selectivities and yields in the arylation of small primary amines compared to previously reported YPhos ligands. Even MeNH(2) and EtNH(2) could be coupled at room temperature with a series of aryl chlorides in high yields.